Au Nanoparticles@Si Nanowire Oligomer Arrays for SERS: Dimers Are Best - Bartschmid, Theresa; Menath, Johannes; Römling, Lukas; Vogel, Nicolas; Atalay, Furkan; Farhadi, Amin; Bourret, Gilles R. (ACS Applied Materials and Interfaces, 2024)
We report the synthesis of vertically aligned silicon nanowire (VA-SiNW) oligomer arrays coated with Au nanoparticle (NP) monolayers via a combination of colloidal lithography, metal-assisted chemical etching, and directed NP assembly. Arrays of SiNW monomers (i.e., isolated NWs), dimers, and tetramers are synthesized, decorated with AuNPs, and tested for their performance in surface-enhanced Raman spectroscopy. The ∼20 nm AuNPs easily enter within the ca. 40 nm gaps of the SiNW oligomers, thus reaching the hot spot region. At 785 nm excitation, the AuNPs@SiNW dimer arrays provide the highest Raman signal, in agreement with electromagnetic simulations showing a high electric field enhancement at the Au/Si interface within the dimer gap region.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Au nanoparticles; colloidal lithography; dimers; metal-assisted chemical etching; SERS; silicon nanowires